Media ownership in the age of convergence - Williams, Granville (Henry Stewart Talks, 2010)
Why rules on media ownership are seen as an essential component of democracy, Theoretical perspectives, Negative example: the role of the media in Nazi Germany, Contemporary experiences and case studies: Rupert Murdoch and News Corporation, Silvio Berlusconi and Italian media and politics, Are rules on media ownership irrelevant in the age of the internet and digital plenitude?, Threats to traditional media from rise of internet
Archived at 2022/04/12